PROFESSIONAL IDENTITY AND VALUE ORIENTATIONS OF A NEW UKRAINIAN SCHOOL TEACHER - Radzimovska, Oksana (Personality and environmental issues, 2026)
In the context of reforming general secondary education in Ukraine, implementing the New Ukrainian School (NUS) concept, and facing the challenges of wartime, the problem of forming a stable professional identity of the teacher as a bearer and transmitter of humanistic values becomes paramount. The article focuses on concepts that are interrelated and complement one another, broadening and deepening the content of the identity phenomenon, yet described by some authors as synonymous: teacher identity, pedagogical identity, and professional identity of the teacher. Pedagogical identity is a systemic value of modern education. In the context of the NUS, a mature pedagogical identity ensures the implementation of partnership pedagogy, serves as a resource for the psychological resilience of teachers and students in wartime conditions, and is a prerequisite for the formation of students' national identity. A blurred pedagogical identity leads to a decline in the teacher's authority, the reproduction of authoritarian interaction models, and undermines the value potential of education. The article reveals the essence of the teacher's professional identity as a dynamic, value-driven construct occupying an intermediate position between personal and social identity. A four-component structure of pedagogical identity is presented (cognitive-reflective, value-semantic, emotional-affective, and behavioral-activity components), its criteria are defined (reflective-cognitive, value-semantic, emotional-identificatory, behavioral-authentic), along with three levels of identity formation (diffuse, forming, and mature). It is substantiated that a well-formed professional identity acts as a factor of the teacher's psychological readiness for creative activity, facilitates the free performance of professional functions, raises the level of aspirations, develops an individual style, and enables authentic subject-to-subject interaction within the 'teacher–student' system. Prospects for further research are seen in the development and testing of psychological support programs for the formation of teachers' professional identity within the continuing education system.